Cross-linguistic influence in multilingual language acquisition: The role of L1 and non-native languages in English and Catalan oral production - Ortega, Mireia (Íkala, Revista de Lenguaje y Cultura, 2008)
Most research in third language acquisition has focused on the effects that factors such as language distance, second language (L2) status, proficiency or recency have on the choice of the source language (L1) in cross-linguistic influence (CLI). This paper presents a study of these factors, and of the influence that the L1 (Spanish) has on L2 (English) and L3 (Catalan) oral production. Lexical and syntactic transfer are analysed in the production of Catalan and English of two multilingual speakers with similar knowledge of non-native languages. They were interviewed twice in an informal environment. The results show that the L1 is the main source of transfer, both in L2 and L3 production, but its influence decreases as proficiency in the target language increases. Language distance also plays an important role in CLI, especially if proficiency in the source language is high and if there has been recent exposure to it. The findings also suggest that while syntactic transfer is exclusively L1-based, lexical transfer can occur from a non-native language. Received: 16-11-2007 /Accepté: 11-02-2008 How to reference this article: Ortega, Mireia. (2008). Cross-linguistic influence in multilingual language acquisition: The role of L1 and non-native languages in English and Catalan oral production. Íkala. 13(1), pp.121-142.